HUBUNGAN SPIRITUALITAS TERAPIS DENGAN PRAKTIK KLINIS TERAPI MUSIK - Feberina Charista; Monica Subiantoro (MANASA, 2018)
This study aims to find out the effects of music therapists’ spirituality in their clinical practice. This qualitative research includes semi-structured interviews with four resource persons who are practitioners in the field of music therapy in Jakarta, Indonesia. Based on the analysis of the interviewee's transcripts, it was found that spirituality and clinical practice of music therapy influence each other. The spiritual values contained in a spiritual identity become the foundation of a therapist in responding events that occur in the practice of music therapy. Conversely, through the practice of music therapy therapists are also reminded of the spiritual values that may be applied. The discussion includes spiritual values related to the practice of music therapy, namely the use of repertoires in music therapy and perspectives that affect the therapeutic process.